PERAN KEPERAWATAN GERONTIK DALAM MENINGKATKAN KUALITAS HIDUP LANSIA - Hasifah, Hasifah (Jurnal Multidisipliner Bharasumba, 2024)
Introduction: Older adults often face health challenges, including chronic diseases, decreased physical function, and mental changes. The role of gerontic nursing includes an in-depth understanding of the various health conditions common in older adults and the ability to provide care that suits their needs. By understanding the physical and psychological changes that occur with increasing age, gerontic nurses can design appropriate interventions to improve the quality of life of older people. Method: This research method uses a literature review where research data is collected using data based on Google Scholar, PUBMED and SAGE. Results: The results of the research showed that from data based PUBMED got 2 articles, SAGE got 3 articles and data based on Google Scholar got 3 articles which were in accordance with the research. Conclusions and Recommendations: The conclusion in this study is that research shows the need for an integrated care approach for the elderly. Integrating aspects of physical, psychological and social health in one care model can be the key to success in improving the quality of life of the elderly. It is hoped that the suggestions in this research will contribute to a better understanding of the importance of psychosocial aspects in nursing services for the elderly, and at the same time provide a basis for the development of more effective interventions.